Model-Based Tools for Pharmaceutical Manufacturing Processes - Gernaey, Krist V. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue on "Model-Based Tools for Pharmaceutical Manufacturing Processes" will curate novel advances in the development and application of model-based tools to address ever-present challenges of the traditional pharmaceutical manufacturing practice as well as new trends. This book provides a collection of nine papers on original advances in the model-based process unit, system-level, quality-by-design under uncertainty, and decision-making applications of pharmaceutical manufacturing processes.